Identifikasi Faktor Penentu Profitabilitas BPR di Kota Batam - Poniman; Hermaya Ompusunggu (Komunitas Dosen Indonesia, 2024)
P This research was conducted to examine the influence of financial ratios that influence the financial performance of Return on Assets (ROA) at Rural Credit Banks in the city of Batam, such as Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Operational Costs, Operational Income (BOPO), Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM). This research is explanatory research with a quantitative approach. The population in this study is all BPRs in the city of Batam for the 2020-2023 research period. The sample for this research was 21 BPRs determined using a purposive sampling method. The research data is in the form of secondary data and the data collection technique is documentation techniques. The analysis technique in this research uses multiple linear regression analysis with the help of the Eviews 10 statistical application. The results of the analysis show that partially CAR and BOPO have a significant negative influence on ROA, LDR and NIM have a significant positive influence on ROA and NPL has no influence on BPR's ROA. is in Batam city.